The role of humans in the development, survival and conservation of semi-dry grasslands in Central-Europe - Illyés, Eszter; Mezei, Tamás (Acta Scientiarum Socialium, 2011)
The paper makes an attempt to approach grasslands with a holistic view: as parts of nature and simultaneously as the scene of different activities of humans. The paper gives a short review on the history and the actual state of grasslands with special focus on Hungarian semi-dry grasslands. It emphasizes the major role of humans even in the formation, the development, the maintenance and conservation of European grasslands. Land use history of European semi-dry grasslands is sketched and the importance of traditional management in the existence of highly valued diverse grasslands is pointed out. The negative effects of recent anthropogenic factors threatening the existence and diversity of semi-dry grasslands in Europe in Hungary are estimated and conservation actions taken to prevent further deterioration are mentioned. The paper comes to the conclusion that maintenance of high-diversity semi-dry grasslands is only possible with the re-introduction of traditional farming systems at landscape scale.
Keywords: land use history; traditional farming; management; maintenance